Acute Hepatopancreatic Necrosis Disease (AHPND): An Emerging Threat to the Shrimp Aquaculture Industry - Ngasotter, Soibam; Mukherjee, Susmita; Bharti, Deeksha (Chronicle of Bioresource Management, 2023)
Acute Hepatopancreatic Necrosis Disease(AHPND) is an emerging shrimp disease caused primarily by certain virulent Vibrio parahaemolyticus strains possessing a plasmid with a gene that encodes for Pir A and Pir B toxins. AHPND affects many shrimp species, notably Penaeus monodon (giant tiger prawn) and Litopenaeus vannamei (whiteleg shrimp) in their post-larval stages within 30-35 days after stocking and can cause mass mortalities up to 100%. AHPND causes devastating economic losses of about billions of dollars annually to the shrimp aquaculture industry. The pathogen primarily targets gut-associated organs and tissue and therefore causes clinical symptoms such as pale and shrunken hepatopancreas, an empty stomach, and an empty gut. Proper diagnosis and treatment methods are necessary to control and prevent further outbreaks. This article highlights the history of AHPND, its causative agent, vulnerable shrimp species, signs and symptoms, diagnosis and detection methods, and control and prevention methods of AHPND.